Estimation of model ice properties in ice tank operations with numerical models - von Bock und Polach, Rüdiger Ulrich Franz; Klein, Marco; Reimer, Nils; Hartmann, Moritz (POAC, 2023)
Conducting model ice tests is still the state of the art in predicting the performance of ships and structures in ice. This is also valid for other occurrences such as waves in ice or ice feature formation processes. In an ice tank ice properties such as the flexural strengths and the thickness usually formulate the target properties towards which the ice production process is adjusted. This also means that prior to testing the properties are measured and in case target properties are not yet met additional tempering or cooling is done until target conditions are met. Conducting cantilever beam tests for the flexural strength and plate deflection tests for the elastic modulus is time consuming in the time critical ice production process. The plate deflection tests itself can take up to an hour including all preparation This paper presents a method that reduces the time needed to conduct property tests in the ice tank, while providing deeper insight into the ice properties. The first method uses a parametric finite element model, which reproduces the cantilever beam tests. With an iterative routine, the elastic or strain modulus of the ice is determined as well as the nominal stress at failure (flexural stress), the elastic stress at the root corners and the buoyancy force. Especially, the latter is in some cases of particular interest and it has been for decades under debate whether this can be read from the force recordings of the cantilever beam tests. The method increases the amount of information of the ice sheet properties significantly and reduces the time spent on ice property testing. The methods are applied and tested for different ice sheets and measurements from the Hamburg Ship Model Basin (HSVA). It is shown that the elastic modulus can be determined with a good agreement (better than 4% for regular model ice of around 30 mm thickness) to the plate deflection tests. Furthermore, the effective strain modulus and the buoyancy force is delivered as result.